Antifungal Activity of Citrus Essential Oil in Controlling Sour Rot in Tahiti Acid Lime Fruits - Vanessa Santos Moura; Lara Dias Olandin; Beatriz Saraiva Mariano; Josiane Rodrigues; Fernando Trevizan Devite; Ana Carolina Costa Arantes; Carmen Lucia Queiroga; Adilson Sartoratto; Fernando Alves de Azevedo; Marinês Bastianel (Plants)
Sour rot, caused by Geotrichum citri-aurantii, is a significant post-harvest disease in citrus, resulting in economic losses due to the lack of effective fungicides. This study investigates the antifungal activity of citrus essential oils in controlling sour rot in Tahiti acid lime fruits. Essential oils were extracted via hydrodistillation with chemical composition analyzed by CG-MS and tested in vitro and in vivo. In vitro assays evaluated mycelial growth inhibition at 2 to 32 µL mL−1 concentrations. In vivo trials involved preventive and curative treatments on artificially inoculated fruits stored at 25 °C ± 2, and the results showed that Pera IAC sweet orange oil, at 32 µL mL−1, reduced disease severity by 96% in curative treatments. In contrast, Late IAC 585 willowleaf mandarin oil demonstrated moderate inhibition (44%) at the highest concentration in vitro. The oils did not affect key fruit quality parameters such as juice yield and total soluble solids. These findings suggest that citrus essential oils could be natural alternatives to synthetic fungicides for post-harvest sour rot management, combining effectiveness with maintaining fruit quality.